(untitled) (JURNAL ADMINISTRASI PUBLIK, 2021)
Empowerment of managers is an effort to emphasize the provision of strength, ability and authority through training and education, counseling, socialization and assistance to managers in managing each type of business being managed. Village Owned Enterprise (BUMDes) is one of the government programs based on empowerment and decentralization, with this program the government has the spirit to rebuild trust with the community to work together to create an economically independent village community. This study uses a qualitative research type where research is descriptive in nature, namely the collection of primary and secondary data is carried out by interview which is then processed and obtained the results. Research results show that the problem that hinders the empowerment of BUMDes managers in Batlale Village is the provision of work programs in the form of savings and loans, business in the marine and plantation sectors. providing infrastructure and business capital which in fact do not have progress and even have not been running due to the level of ability or knowledge of the managers who have not been able to develop their own programs. The training provided by the government on how to manage and develop a business as well its potential only happened 4 years ago. apart from that, there are several obstacles, such as the lack of attention, concern and encouragement from the community and the government in assisting managers in running and developing business programs. The lack of these trainings means that the government only provides outreach on the performance improvement of BumDes managers in Batlale Village. Keywords : Empowerment, Management, program